Cloning and characterization of MgtE, a putative new class of Mg2+ transporter from Bacillus firmus OF4. - Smith, R L (1995)
The MM281 strain of Salmonella typhimurium which possesses mutations in each its three known Mg2+ transport systems and requires 100 mM Mg2+ for growth was used to screen a genomic library from the gram-positive alkaliphilic bacterium Bacillus firmus OF4 for clones that could restore the ability to grow without Mg2+ supplementation. Of the clones obtained, five also conferred sensitivity to Co2+, similar to the phenotype of mutants with mutations in the S. typhimurium corA Mg2+ transport locus. All five contained identical inserts by restriction analysis. Using 63Ni2+ as a surrogate for the unavailable 28Mg2+, the plasmid insert was shown to restore cation uptake with properties similar but not identical to those of the S. typhimurium CorA Mg2+ transporter. Sequence analysis of one clone identified a single open reading frame with multiple possible initiation sites. Deletion and mutation analysis identified a minimum open reading frame of 939 bp encoding a polypeptide with a predicted molecular mass of 34 kDa. Disruption of the open reading frame eliminated cation influx activity and restored resistance to Co2+. This putative transporter, designated MgtE, has no sequence similarity to any known protein including CorA and appears to represent a new class of Mg2+ transport system.